Determining appropriate loss coefficients for use in the nozzle-model of a stage-by-stage turbine model - Marx, Alton Cadle (Department of Mechanical Engineering, 2020)
A previously developed turbine modelling methodology, requiring minimal blade passage information, produced a customizable turbine stage component. This stage-by-stage turbine nozzlemodel component was derived from the synthesis of classical turbine theory and classical nozzle theory enabling the component to accurately model a turbine stage. Utilizing Flownex, a thermohydraulic network solver, the turbine stage component can be expanded to accurately model any arrangement and category of turbine. This project focused on incorporating turbine blade passage geometrical information, as it relates to the turbine specific loss coefficients, into the turbine stage component to allow for the development of turbine models capable of predicting turbine performance for various structural changes, anomalies and operating conditions. The development of turbine loss coefficient algorithms as they relate to specific blade geometry data clusters required the investigation of several turbine loss calculation methodologies. A stage-by-stage turbine nozzle-model incorporating turbine loss coefficient algorithms was developed and validated against real turbine test cases obtained from literature. Several turbine models were developed using the loss coefficient governed turbine stage component illustrating its array of capabilities. The incorporation of the turbine loss coefficient algorithms clearly illustrates the correlation between turbine performance deviations and changes in specific blade geometry data clusters.